2018
DOI: 10.1016/j.icarus.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Increase in cratering efficiency with target curvature in strength-controlled craters

Abstract: Impact-cratering processes on small bodies are thought to be mainly controlled by the local material strength because of their low surface gravity, and craters that are as large as the parent bodies should be affected by the target curvature. Although cratering processes on planar surfaces in the strength-controlled regime have been studied extensively, the mechanism by which target curvature affects the cratering processes remains unclear. Herein, we report on a series of impact experiments that used spherica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, the intercept of that curve will provide the value of P once 0 is calculated. Laboratory impact experiments have shown that cratering efficiency may increase when the size of the crater becomes comparable to the target boulder size [45]; however, this is thought to be due to spallation, which is not a dominant mechanism for the craters we observe on Bennu's surface.…”
Section: Transition From Cratering To Catastrophic Disruptionmentioning
confidence: 78%
“…Furthermore, the intercept of that curve will provide the value of P once 0 is calculated. Laboratory impact experiments have shown that cratering efficiency may increase when the size of the crater becomes comparable to the target boulder size [45]; however, this is thought to be due to spallation, which is not a dominant mechanism for the craters we observe on Bennu's surface.…”
Section: Transition From Cratering To Catastrophic Disruptionmentioning
confidence: 78%
“…The Gibeon blocks in this study are small compared to the crater size. For brittle targets, the tensile strength is much lower than compressive or shear strength; therefore, when the target is small, the rarefaction waves generated at the free surface affect the spall diameter and total crater volume, with the topographic profile of the central pit being unaffected (Suzuki et al, 2018).…”
Section: Measurement Resultsmentioning
confidence: 99%
“…Note that spallation in porous gypsum targets often produces large fragments (e.g., Fig. 3 in Suzuki et al 2018). Such a process with large crack propagation is highly probabilistic; hence, the surface (spall) diameter D s /D p for porous gypsum may scatter.…”
Section: Scaling By Conventional Crater Scaling Lawmentioning
confidence: 99%